(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article examines the history and current state of terminology in the Spanish language. A brief overview shows the state of Spanish-language terminology in Spain and other Spanish-speaking countries. The main ways of forming terminology and the problems of creating terminology systems in the conditions of the information society are analyzed. In conclusion, some recommendations are given for the development of translation competencies when teaching Spanish for professional purposes.